VARIETY OF “KOPIKO” PRODUCT PLACEMENT IN VINCENZO'S KOREAN DRAMA ON TELEVISION: WHAT ARE THE ETHICS? - Ni Made Ras Amanda Gelgel; I Gusti Agung Ayu Rahma Praminia; Ni Luh Ramaswati Purnawan (Profetik: Jurnal Komunikasi, 2022)
Product placement or embedded marketing is a marketing technique that unites products or brands in activation or program, such as television programs, events, sports, video games, or movies. This technique is now often found on the screen of Sinetron in Indonesia. For this reason, this study aims to identify the variety of product placement in Sinetron Indonesia to be studied from the perspective of broadcasting ethics in Indonesia. The object of this research is the Korean drama Vincenzo. The concept of product placement used in this research is according to d'Astous and Sequin and Přikrylová dan Jahodová. The research method is descriptive qualitative with a study of visual data documentation on these four episodes of the Korean drama Vincenzo. The research found that the variety of product placement used is Integrated Explicit Product Placement. The actor plays an active role in the scene and is expressed formally in the program or plot. The main star clearly shows the attributes and benefits of the central hat. This product placement is no longer implicit or sponsorship but more open. Ethically this can psychologically impact the audience that this is not part of an advertisement but a Sinetron scene. This strategy does not protect the audience. It is because the message is disguised not as an advertisement but as a persuasion function.